Developing Entrepreneurial Competences Through Professional Noticing : Findings of the Empirical Study - Ahokas, Ira; Grönlund, Mikko; Grundschober, Isabell; López-Varela, Asunción; Finkel, Lucila; Alonso, David; Carty, Anthony; Kelly, Kathy (My University, 2026)
This Findings Report brings together the results of an international study exploring how Professional Noticing supports the development of entrepreneurial competences. The report also outlines national insights, and practical recommendations and the conditions that help Professional Noticing take root in different educational settings.